The Influence of Information, Communication, and Technology (ICT) on Students' Learning Motivation in English Language Learning at Higher Education Institutions - Jamilah, Nur; Fatkhurrozi, Anang; Siswoyo, Selina Rahmawati (STAI Nurul Islam Mojokerto, 2024)
This study investigates the impact of Information and Communication Technology (ICT) on students' learning motivation in English language learning at higher education institutions. As the digital era evolves, ICT plays a pivotal role in enhancing education by offering broader access to learning resources and promoting student engagement. The research focuses on how ICT usage influences learning motivation, particularly in English, where motivation is critical for academic and professional success. Data were collected from 30 students through questionnaires, measuring motivation levels before and after ICT implementation. Regression analysis revealed a significant positive relationship between ICT usage and learning motivation, with 54.4% of motivation variability explained by ICT use. The study found that ICT increased students' interest, active participation, and accessibility to learning materials. Despite its benefits, challenges such as unequal access to technology and varying digital literacy levels were identified. The study concludes with recommendations for improving ICT integration through training, infrastructure development, and continuous evaluation. These findings contribute to the understanding of ICT’s role in fostering motivation in English language learning, offering insights for educators and policymakers to design more effective learning environments.